Mycobacterium tuberculosis Rv0928 protein facilitates macrophage control of mycobacterium infection by promoting mitochondrial intrinsic apoptosis and ROS-mediated inflammation - Xu, Chenling; Yue, Yan; Xiong, Sidong (Frontiers in Microbiology, 2023)
Macrophages are the main target cells for Mycobacterium tuberculosis (Mtb) infection. Previous studies have shown that Mtb actively upregulates phosphorus transport proteins, such as Rv0928 protein (also known as PstS3), to increase inorganic phosphate uptake and promote their survival under low phosphorus culture conditions in vitro. However, it is unclear whether this upregulation of PstS3 affects the intracellular survival of Mtb, as the latter is also largely dependent on the immune response of infected macrophages. By using Rv0928-overexpressing Mycobacterium smegmatis (Ms::Rv0928), we unexpectedly found that Rv0928 not only increased apoptosis, but also augmented the inflammatory response of infected macrophages. These enhanced cellular defense mechanisms ultimately led to a dramatic reduction in intracellular bacterial load. By investigating the underlying mechanisms, we found that Rv0928 interacted with the macrophage mitochondrial phosphate carrier protein SLC25A3, reduced mitochondrial membrane potential and caused mitochondrial cytochrome c release, which ultimately activated caspase-9-mediated intrinsic apoptosis. In addition, Rv0928 amplified macrophage mitochondrial ROS production, further enhancing pro-inflammatory cytokine production by promoting activation of NF-κB and MAPK pathways. Our study suggested that Mtb Rv0928 up-regulation enhanced the immune defense response of macrophages. These findings may help us to better understand the complex process of mutual adaptation and mutual regulation between Mtb and macrophages during infection.